2018
DOI: 10.1071/an16784
|View full text |Cite
|
Sign up to set email alerts
|

Feeding wet distillers grains plus solubles contributes to sarcoplasmic reticulum membrane instability

Abstract: Abstract. Feeding wet distillers grains plus solubles (WDGS) increases polyunsaturated fatty acid (PUFA) levels in beef. It was hypothesised that WDGS in feedlot diets increases PUFA concentration in the sarcoplasmic reticulum (SR) membrane, thereby altering membrane integrity, resulting in more rapid intracellular calcium leakage and improved tenderness. The objective of this study was to evaluate this hypothesis. Ninety-six crossbred steers were fed either a corn-based diet with 0% WDGS or 50% WDGS. Fifteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 55 publications
(57 reference statements)
5
17
1
Order By: Relevance
“…The average sarcomere length of strip loins from cattle fed corn-only, de-oiled MDGS, de-oiled MDGS plus corn oil, and full-fat MDGS were 1.77, 1.76, 1.75, and 1.76 μm, respectively. In agreement with our results, no differences in sarcomere length have been reported in studies on feeding distillers grains (Oltra et al, 2008: Chao et al, 2017a, 2017b.…”
Section: Sarcomere Lengthsupporting
confidence: 94%
See 4 more Smart Citations
“…The average sarcomere length of strip loins from cattle fed corn-only, de-oiled MDGS, de-oiled MDGS plus corn oil, and full-fat MDGS were 1.77, 1.76, 1.75, and 1.76 μm, respectively. In agreement with our results, no differences in sarcomere length have been reported in studies on feeding distillers grains (Oltra et al, 2008: Chao et al, 2017a, 2017b.…”
Section: Sarcomere Lengthsupporting
confidence: 94%
“…No differences in troponin-T degradation were found between dietary treatments 2 d postmortem (P = 0.60; Table 3). In agreement with our results, Chao et al (2017a) showed that the inclusion of 50% WDGS in finishing diets did not affect troponin-T degradation when compared with diets with no addition of WDGS in any of the aging periods studied: 2, 7, 14, or 21. Conversely, Chao et al (2017b) indicated that feeding 40% WDGS increased troponin-T degradation at 2 d of aging compared with no addition of WDGS.…”
Section: Troponin-t Degradationsupporting
confidence: 92%
See 3 more Smart Citations